PENGARUH LATIHAN CLAP PUSH UP TERHADAP HASIL TOLAK PELURU PADA SISWA KELAS X ATP3 SMK PERTANIAN PEKANBARU - Siregar, Gorby Hatiha; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT: The problem in this research is the lack of strength of arm and shoulder muscles, it is seen from the results of the bullet is not the maximum repulsion or does not reach the minimum completeness criteria specified Agricultural vocational school Pekanbaru. Forms of this research is experimental study, using total sampling technique obtained a sample of 15 people. The instrument used in this study is the use of roll meter, which aims to measure the results of shot put. Once it is done Pree test and treatment exercise for 16 sessions with 15 students of class X SMK Agriculture ATP3 Pekanbaru and then performed post test. Though with statistical data, to test for normality with lilifors test at significant level 0,05α. The hypothesis is the influence of exercise clap push-ups on the shot put results in class X SMK Agriculture ATP3 Pekanbaru. Based on the analysis of statistical data, there are an average Pree-test of 76.84 and the average post-test of 116.12, then the data is normally distributed. Based on t test analysis produces Thitung of 11.90 and Ttabel 1,761, meaning Thitung> Ttabel. Then, there is the Effect of Exercise clap push-ups on the shot put results of class X SMK Agriculture ATP3 Pekanbaru. Keywords: Clap push up, shot put